EFEKTIVITAS KEGIATAN BERMAIN CAT AIR UNTUK MENINGKATKAN KEMAMPUAN MENGENAL WARNA BAGI ANAK TUNAGRAHITA RINGAN KELAS D II/C DI SDLB N 20 NAN BALIMO KOTA SOLOK - Nadia Derara, Asep Ahmad Sopandi, Elsa Efrina (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was beckground by the problems in mild mental retardation child in second grade in SDLB N 20 Nan Balimo Solok who has problems in recognizing colours. Under these conditions, the researchers want to prove that with a waterpaint play activities can improve the ability to know the colour (red, blue, yellow) mild mental retardation child in the second grade in SDLB N 20 Nan Balimo Solok. This research use Single Subject Research type, with ABA design and data analysis techniques using visual analysis chart. Result of this study shows that the activity play waterpaint can improve the ability to know the colour of the mild mental retardation child in second grade in SDLB N 20 Nan Balimo Solok.